2019
DOI: 10.3390/f10080668
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Season of the Year on the Frequency and Degree of Damage during Commercial Thinning in Black Alder Stands in Poland

Abstract: The aim of this study was to investigate the effect of season of the year on the frequency and degree of damage to residual trees caused during winter and summer timber harvesting operations in young alder stands. Analyses were conducted in pure black alder (Alnus glutinosa Gaertn.) stands aged 38 and 40 years, located in north-eastern Poland. Chainsaw logging was performed in the cut-to-length (CTL) system, while timber was extracted using an agricultural tractor with a trailer with manual timber loading and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 25 publications
(30 reference statements)
1
13
0
Order By: Relevance
“…This is quite consistent with the practice of mountainous ground-based harvesting operations to immediately prepare the logs for further transportation [32,34]. In the majority of previous studies, they were treated as two separate practices, mainly due to unfavorable weather conditions and the short duration of the felling period [36]. Generally, harvesting contractors prefer to apply hot systems in which felling and processing operations are synchronized.…”
Section: Discussionsupporting
confidence: 62%
“…This is quite consistent with the practice of mountainous ground-based harvesting operations to immediately prepare the logs for further transportation [32,34]. In the majority of previous studies, they were treated as two separate practices, mainly due to unfavorable weather conditions and the short duration of the felling period [36]. Generally, harvesting contractors prefer to apply hot systems in which felling and processing operations are synchronized.…”
Section: Discussionsupporting
confidence: 62%
“…It was also found that tree injuries depend on the season, and can be higher in summer [79], as well as affected by stand structure: in uneven-aged stands, damage can be more frequent, especially among younger trees [76]. Mechanised harvesting tends to cause less damage than using a chainsaw for felling and more damaged trees are observed near strip roads [80,81].…”
Section: Harvesting-stand Interactionmentioning
confidence: 99%
“…There is little information on productivity and labour consumption in the harvesting of timber from alder stands subject to thinning. The reason for this is the presence of alder stands in wetlands, which significantly hinders timber harvesting [15]. In many cases, the potential for using heavy multipurpose machinery is restricted by difficult terrain conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Bembenek et al [16] reports that winters without snow and autumn rainfall can cause a shortening of the period in which it is possible to use forest machines, especially in stands with low load-bearing capacity. According to Grzywiński et al [15], it is particularly important to select the right season, technology, and work organisation, which can significantly reduce environmental damage. The use of large and heavy machines, such as skidders and forwarders, may contribute to soil compaction [17], and later to erosion and ruts, especially visible on skidding trails [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation